Learning Program of English for Tourism Based on Gen-Z Theories - Rheinatus Alfonsus Beresaby; Juliansyah; Bambang Trisno Adi; Alia Afiyati (English Language Education Department, Universitas Majalengka, 2024)
This research is motivated by the fact that the quality of the teaching of the English for Tourism needs to be improved by modifying learning patterns and materials that are more suited to the character of Generation Z. The aim of this research is to provide an overview of the learning process for courses related to tourism so that it matches with the characters of generation Z. This research was carried out using descriptive and experimental methods. It is called descriptive because the researchers describe the learning conditions according to the theme of this research and the completeness of the learning documents. Meanwhile, this research is called experimental because the researcher carried out practical teaching experiences with ideas and learning processes that suit the character and psychological nuances of Generation Z. The results of this research are modifications to the Semester Learning Plan or RPS which was prepared before the experiment was carried out; so that an activity model and learning materials that are appropriate to the research theme were obtained. It is hoped that the results of this research can provide inspiration for similar learning in other courses.